Konsep Etika Murid Terhadap Guru Menurut Habib Abdullah Bin Alawi Al-Haddad (Studi Analisis Kitab Adab Suluk Al-Murid) - Ainun Putri Wulandari, M. Ma’ruf (Al-Makrifat: jurnal kajian Islam, 2020)
This study analyzes the thoughts of Habib Abdullah bin Alawi Al-Haddad about student ethics to teachers in kitab Adab Suluk Al-Murid. The purpose of this study: (1) To determine the ethical concepts of students towards teachers according to Habib Abdullah bin Alawi Al-Haddad. (2) To find out the application of students ethical concepts to teachers according to Habib Abdullah bin Alawi Al-Haddad in educational institutions today. This type of research uses library research. The results showed that the concept of student ethics to teachers according to Habib Abdullah bin Alawi Al-Haddad is a description of the ethics of students to teachers to gain useful knowledge. The application of ethics in educational institutions today can be done through character education, teaching methods, learning, teacher modeling, and also supported by student awareness to implement them.